Polysaccharide of Atractylodes macrocephala Koidz (PAMK) Alleviates Cyclophosphamide-induced Immunosuppression in Mice by Upregulating CD28/IP3R/PLCγ-1/AP-1/NFAT Signal Pathway - Xiang, Xuelian; Cao, Nan; Chen, Feiyue; Qian, Long; Wang, Yifei; Huang, Yunmao; Tian, Yunbo; Xu, Danning; Li, Wanyan (Frontiers in Pharmacology, 2020)
The polysaccharide of Atractylodes macrocephala Koidz (PAMK) is recognized as an immune enhancer, with anti-cancer, anti-tumour, lymphocyte-activating and lymphocyte proliferation-inducing effects. The purpose of this study was to investigate the mechanism by which PAMK alleviates the decline in T cell activation induced by CTX. Twenty-four 5-week-old BALB/c female mice were randomly divided into four groups (C, PAMK, CTX, PAMK+CTX). In vivo, the spleen index, spleen cell morphology and apoptosis, cytokine concentration, T cell activating factor (CD25, CD69, CD71), mRNA and protein expression levels related to the CD28 signalling pathway were determined. The Th1/Th2 ratio, activating factor, mRNA and protein expression levels related to the CD28 signalling pathway were determined by isolation and culture of lymphocytes in vitro. The results showed that PAMK significantly improved the spleen index, alleviated abnormal lymphocyte morphology and apoptosis, maintained the balance of Th1/Th2 cells, increased the levels of IL-2, IL-6, TNF-α, and IFN-γ, and increased the gene and protein expression levels of CD28, PLCγ-1, IP3R, NFAT, and AP-1. In conclusion, PAMK alleviated the decline in activation level of lymphocytes induced by CTX by upregulating CD28 and downstream signalling pathways and finally increasing cytokine secretion.